The Influence of Work Discipline, Compensation, and Job Stress on The Performance of Maxim Bike Online Transportation Drivers in Makassar City - Irfan Hanif Natsir; Moh. Aris Pasigai; Nasrullah Nasrullah (International Journal of Business and Quality Research, 2025)
This research aims to determine the influence of work discipline, compensation and work stress on the performance of Maxim Bike drivers in Makassar City. The population in this research is Maxim Bike drivers in Makassar City. The sampling technique used purposive sampling technique so that a sample of 40 respondents was determined. Data collection methods were carried out by observation, questionnaires, and interviews. The data analysis methods used were descriptive analysis, instrument testing, classical assumption testing, and multiple linear regression analysis. The research results show that work discipline and work stress have a positive and significant effect on the performance of Maxim Bike drivers, while compensation does not have a positive and significant effect on the performance of Maxim Bike drivers. The multiple linear regression model shows that work discipline, compensation, and work stress are three factors that affect good performance, so before good performance can be achieved, work discipline, compensation and work stress must be met.